COPD in nonsmokers: Reports from the Tunisian population-based burden of obstructive lung disease study - Denguezli, M; Daldoul, H; Harrabi, I; Gnatiuc, L; Coton, S; Burney, P; Tabka, Z; Gnatiuc, L (Public Library of Science, 2016)
Background It’s currently well known that smoking and increasing age constitute the most important risk factors for chronic obstructive pulmonary disease (COPD). However, little is known about COPD among nonsmokers. The present study aimed to investigate prevalence, risk factors and the profiles of COPD among nonsmokers based on the Tunisian Burden of Obstructive Lung Disease (BOLD) study. Methods 807 adults aged 40 years+ were randomly selected from the general population. We collected information about history of respiratory disease, risk factors for COPD and quality of life. Post-bronchodilator spirometry was performed for assessment of COPD. COPD diagnostic was based on the post-bronchodilator FEV1/FVC ratio, according to the Global Initiative for Obstructive Lung Disease (GOLD) guidelines. The lower limit of normal (LLN) was determined as an alternative threshold for the FEV1/FVC ratio. Results and Conclusions Among 485 nonsmokers, 4.7% met the criteria for GOLD grade I and higher COPD. These proportions were similar even when the LLN was used as a threshold. None of the nonsmokers with COPD reported a previous doctor diagnosis of COPD compared to 7.1% of smokers. Nonsmokers accounted for 45.1% of the subjects fulfilling the GOLD spirometric criteria of COPD. Nonsmokers were predominately men and reported more asthma problems than obstructed smokers. Among nonsmokers significantly more symptoms and higher co-morbidity were found among those with COPD. Increasing age, male gender, occupational exposure, lower body mass index and a previous diagnosis of asthma are associated with increased risk for COPD in nonsmokers. This study confirms previous evidence that nonsmokers comprise a substantial proportion of individuals with COPD. Nonsmokers with COPD have a specific profile and should, thus, receive far greater attention to prevent and treat chronic airway obstruction.